Participatory Watershed Development: A Case Study of Antisar Watershed in Gujarat State - G. L. Bagdi and R. S. Kurothe, (Indian Journal of Extension Education, 2013)
The study was conducted during 1997-2003 in the Integrated Wasteland Development Project (IWDP), Antisarwatershed, located in Kapadwanj Taluka of Kheda district in Gujarat state in India. The Antisar watershed was developedin participatory mode by involving local people in decision making and adoption of various soil and water conservation(SWC) interventions for sustainable development. In the participatory watershed development process, a set of suitabletechnologies were tested by farmers on their farm as well as community land in the watershed area with their partcontribution as money or labour and under guidance of multidisciplinary team of scientists of Project ImplementingAgency (PIA). Bottom-up approach was adopted in the Antisar watershed development by involving the local farmers totake decisions in planning, implementation and maintenance of SWC practices adopted for the watershed development.The participation of male and female beneficiary farmers was high in the watershed development programme. The Antisarwatershed development programme was fruitful up to the satisfaction of farmers as well as scientists of PIAto mitigate thewater scarcity condition in the area due to ground water recharge for sustainable agricultural production.